Determinants of Commercial Bank Profitability in Vietnam - Tiep, Nguyen Anh; Thanh, Bui Dan; Ha, Doan Thanh; Nga, Nguyen Thi Ngoc (Archives of Business Research, 2022)
This article aims to study and point out the impact of internal and external factors on the profitability of joint-stock commercial banks during 2009-2020. The research team has used a data sample of 24 joint-stock commercial banks accounting for a large proportion of the total assets of the Vietnamese commercial banking system. The factors included in the research model are bank size, equity size, outstanding loans, provision for credit losses, operating costs, liquidity, income diversification, bank income diversification, and the inflation rate, while the bank profitability variable is represented by two variables - ROE and ROA. Through fixed effect regression FEM and random effect regression REM analyses, on one hand, the final results revealed that ROA has a positive relationship with size of equity, liquidity, income diversification and inflation; however, it is negatively related to operating costs. On the other hand, ROE has a positive impact among bank size, outstanding loans, liquidity, income diversification; yet a negative impact to equity size and operating costs. From the research results, the authors propose some policy implications to increase the profitability of commercial banks in Vietnam.